KERANGKA HUKUM PENETAPAN HARGA TANDAN BUAH SEGAR (TBS) SAWIT: URGENSI REGULASI, KEADILAN HARGA BAGI PETANI, DAN MEKANISME SENGKETA HARGA - Loso Judijanto (JOURNAL OF LAW AND NATION, 2026)
Indonesia’s palm oil industry faces serious structural challenges regarding price fairness for smallholders, particularly independent farmers who are not part of a partnership scheme. This study analyses the legal framework for setting the price of Fresh Fruit Bunches (FFB) with a focus on the urgency of regulation, price fairness for farmers, and price dispute mechanisms. The method used is a literature review (library research) with a juridical-normative approach to analyse legislation, scientific journals, and relevant official publications. The research findings indicate that although regulations are in place through Ministry of Agriculture Regulation No. 01/Permentan/KB.120/1/2018 and Ministry of Agriculture Regulation No. 13 of 2024, implementation on the ground remains weak due to the absence of strict sanctions for violators of reference prices and a significant enforcement gap. Independent farmers receive an average TBS price 15–25% lower than partner farmers with the same fruit quality due to weak bargaining power, information asymmetry, and a long distribution chain. Existing dispute resolution mechanisms are also ineffective due to the absence of specialised arbitration or mediation bodies and the lack of independent oversight mechanisms. This study recommends comprehensive reforms encompassing strengthened regulations with strict sanctions, the establishment of an independent oversight body, the digitisation of price information, and equitable partnership contracts to foster fairness and the sustainability of the national palm oil industry.